THE DEVELOPMENT OF DEFENCES IN UNFAIR DISCRIMINATION CASES (PART 2) - Jonathan Partington; Adriaan van der Walt (Obiter, 2022)
All anti-discrimination legislation that applies in the employment context contains defences to or justifications for discrimination. In South Africa, the defences available against a discrimination claim in the employment context are contained in the Employment Equity Act 55 of 1998.The Employment Equity Act gives only a basic structure of a prohibition on unfair discrimination. It is left to our courts to give content to and develop discrimination law. It is within this context that the Employment Equity Act expressly mentions “affirmative action consistent with the purpose” of the Employment Equity Act and “an inherent requirement of a job” as two specific exceptions to the right to equal treatment. The Employment Equity Act does not, however, state these exceptions to be a numerus clausus. It has been questioned whether there may, in addition to the statutory exceptions, be a residual “general fairness” defence to a claim of unfair discrimination.The development of the defences in South Africa is discussed and it is concluded that any possible derogations from the right to equal treatment must be strictly construed. This conclusion is mandated by the wording of the legislation itself and the influence of the Constitution. Accordingly, the notion of an implied “general fairness” defence is not supported. The remaining defences, it is submitted, should develop within the parameters of established principles in a disciplined manner, having due regard for the achievement of substantive equality.